Demand for University Education and Students’ Employment Prospects in Nigeria - Ajadi, Timothy Olugbenga (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2023)
Employment prospects of Nigerian undergraduates remain questionable while demand for university education is on the increase. This study, adopted descriptive research design. A sample of 380 students of public universities in Osun State, drawn from 36,333 undergraduates of Obafemi Awolowo University, Ile-Ife and Osun State University, Osogbo, were the respondents using multi-stage sampling procedure. A Students’ Employment Prospects and Demand for University Education Questionnaire (SEP-DUEQ) was designed to elicit information from respondents. The result identified decision to become entrepreneur 266(70.9%), acquiring knowledge of intended profession 262(69.8%), earning high salary after graduation 251(66.9%), among others as reasons for demanding university education. The result also showed that employment prospects available to students after graduation include entrepreneurial skills to create job 298(78.5%), sufficient job opportunity in private-sector organisations 252(67.2%) and high access to fund to start businesses 235(62.7%). The study recommends that university education in Nigeria should be restructured to enhance students’ employment prospects